Global unification of Business Valuation Standards = Proces unifikacji standardów wyceny przedsiębiorstw na świecie - Szczepankiewicz, Elżbieta Izabela (Zielona Góra: Faculty of Economics and Management Press)
The paper analyzes the most important standards in the word that can be helpful in building a uniform Polish Business Valuation Standards. The article presents also structure and scope of Standards. The paper also analyzes Polish regulations related to business valuation, and assesses the degree of their convergence with leading standards in the word. The paper also analyzes Polish regulations related to business valuation, and assesses the degree of their convergence with leading global standards. Research method adopted in the study is to analyze the most important standards in the word and inference.
Keywords: standardy wyceny przedsiębiorstw; Business Valuation Standards